PENGARUH ENTREPRENEURIAL LEADERSHIP DAN INNOVATION CAPACITY TERHADAP COMPETITIVE ADVANTAGE PADA USAHA KECIL DAN MENENGAH (UKM) BINAAN DINAS PERDAGANGAN KOTA SURABAYA - Arini Sulistyowati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2018)
The contribution of Small and Medium Enterprises (SMEs) to economic growth makes the performance of SMEs need to be improved, but in creating the optimal performance it needs a competitive advantage that must be owned by every SME. The competitive advantage can be influenced by several factors. This research was conducted with the aim to analyze the influence of entrepreneurial leadership and innovation capacity toward competitive advantage on SMEs of the Trade Service Department of Surabaya City. This study uses a quantitative approach. Data collection was done by distributing questionnaires. Data analysis technique used is analysis of The Structural Equation Model (SEM) with Partial Least Square (PLS) program. The results of this study found that entrepreneurial leadership and innovation capacity have a significant effect on competitive advantage on SMEs of the Department of Commerce Surabaya City.